The effects of alkali treatment on the mechanical and chemical properties of banana fibre and adhesion to epoxy resin - Zin, Mohd Hanafee; Abdan, Khalina; Norizan, Mohd Nurazzi; Mazlan, Norkhairunnisa (Universiti Putra Malaysia Press, 2018)
The main focus of this study was to obtain the optimum alkaline treatment for banana fibre and the its effect on the mechanical and chemical properties of banana fibre, its surface topography, its heat resistivity, as well as its interfacial bonding with epoxy matrix. Banana fibre was treated with sodium hydroxide (NaOH) under various treatment conditions. The treated fibres were characterised using FTIR spectroscopy. The morphology of a single fibre observed under a Digital Image Analyser indicated slight reduction in fibre diameter with increasing NaOH concentration. The Scanning Electron Microscope (SEM) results showed the deteriorating effect of alkali, which can be seen from the removal of impurities and increment in surface roughness. The mechanical analysis indicates that 6% NaOH treatment with a two-hour immersion time gave the highest tensile strength. The adhesion between single fibre and epoxy resin was analysed through the micro-droplet test. It was found that 6% NaOH treatment with a two-hour immersion yielded the highest interfacial shear stress of 3.96 MPa. The TGA analysis implies that alkaline treatment improved the thermal and heat resistivity of the fibre.